Taming the genius loci? Contesting post-socialist creative industries in the case of Brno's former prison. (March 2020) - Alexandrescu, Filip; Osman, Robert; Klusáček, Petr; Malý, Jiří
Abstract: In the increasingly tight race of inter-urban competition, the idea that cities have to be made creative has gripped the imagination of urban planners and scholars alike. This process is imagined as straightforward, readily exportable and devoid of conflict. The paper uses the perspective of relational place-making to reveal the creative city imperative as a political process. This is carried out through the medium of conflict, which brings about two contrasting place frames, which progressively reveal each other's political connections. We use the case of a former central-European prison, located in Brno, the Czech Republic, to show how making a city creative is just one possible framing of a place, how making cities attractive to creative individuals engenders resistance and how historical memory summons the powerful genius loci, that is nevertheless relational and contingent. The results illustrate in detail how the conflict between development and preservation unfolds around six axes of opposition that define the two frames (e.g. future vs. past, part vs. whole etc.) and how these axes are themselves linked to various concepts of place and time. Highlights: The creative city is not a neutral and natural strategy for urban regeneration. Making a city creative is just one possible framing of a place. The creative city imperative is a political process, not a mere planning decision. Dynamics of conflict can shape mechanisms of creative city-making. Instrumentalization of historical memory challenges the creative city thesis.